Legal Certainty of Creditor's Rights in The Fiduciary Agreement - Akanittha Pranoto, William Sudassi; Soemartono, Gatot P. (Universitas Ekasakti, 2023)
Fiduciary guarantee agreements have a unique characteristic called executorial rights, namely the right to execute the same collateral object as a court decision. Executorial Rights provide creditors with protection rights against receiving payments from debtors. The existence of executorial rights was lost because of the Constitutional Court's decision regarding the meaning of executorial rights that the debtor must agree to the occurrence of a breach of contract. This problem has changed the essence of fiduciary guarantees. Therefore, it is necessary to examine the legal certainty regarding the meaning of executorial rights in Constitutional Court Decisions and how to finalize agreements with creditors to ensure the return of their rights is guaranteed. This research was carried out using a normative method with deductive specifications, namely analyzing general-specific matters, aiming to find out about the legal certainty of the executorial rights owned by creditors after the Constitutional Court Decision Number 18/PUU-XVII/2019 and Number 2/ PUU-XIX/2021. The conclusion of this research shows that the Constitutional Court's decision has had a negative impact on fiduciary guarantees in Indonesia. Protection of creditors' rights is reduced and executorial rights become difficult to implement. Parties wishing to enter into a fiduciary agreement must pay attention to the provisions and draw up the agreement carefully, meticulously and in detail to maximize the rights of creditors if a breach of contract occurs during the implementation of the agreement.